Uji Perbedaan Sistem Jajar Legowo Terhadap Beberapa Varietas Padi (Oryza sativa L.) Pada Lahan Sawah Tadah Hujan - Sarlyones Kafisa; Lisa Mawarni; Rosmayati Rosmayati (Universitas Sumatera Utara, 2016)
The row spacing system on varieties of rice (Oryza sativa L.) in rain fed field, guided by Lisa Mawarni and Rosmayati. This research is to know the differences effect of row spacing system to growth and production of rice plant in rain water paddy field. This research had done at Desa Sendang Rejo, Kecamatan Binjai, North Sumatera with the 50 meters of sea level, from April until August 2015. This research used split-plot design with two factors and three replicates. The first factor was row spacing system (square, row spacing 2:1, row spacing 4:1). The second factor was varieties (Ciherang, Mekongga, and IR 64). The result show that the planting system effect was not significant to all parameters but the varieties significantly influence the high plant, tiller numbers, leaf length , weight of panicle per sample, weight of 1000 grain, weight of grain per panicle and production per plot. The interaction significantly influence for plant height 2,3 and 6 weeks after planting (wap), numbers of tillers 2,5 and 6 wap, and weight of grain per panicle. The highest production variety was Ciherang 3,84 kilograms per areas (4,5 m²) and the lowest production was IR 64 variety 2,92 kilograms per areas.